Diversity changes in an intensively bred wheat germplasm during the 20th Century - Christiansen, M.J.; Andersen, S.B.; Ortíz, R. (2002)
Plant breeding may lead to narrowing genetic diversity of cultivated crops, thereby affecting sustained selection gains in crop improvement. A total of 47 microsatellite primer pairs (mapped to the 21 wheat genetic linkage groups) were assessed in 75 Nordic spring wheat cultivars bred during the 20th century to determine the variation of genetic diversity in this germplasm throughout this period. The number of alleles ranged from one to seven, with an average of 3.6 alleles per microsatellite marker. A dendrogram resulting from analysis of the matrix of dissimilarities using the unweighted pair-group method with arithmetic average discriminated all cultivars and revealed clusters of accessions released both from some geographical area in the Nordic Region and the breeding era, i.e. before and after World War II. Genetic diversity in this wheat material increased from 1900 to 1940 and again from 1960 onwards. In between these two periods there was a loss of diversity, which could not be explained by changes in a single genome or in one or few chromosome sets. Effects of different selection within countries are revealed by clear differences in frequency of some microsatellite alleles. In adition some microsatellite alleles were lost during the first quarter of the century while several new alleles were introduced in the Nordic spring wheat material during the second half of the century. These results suggest that genetic diversity in Nordic spring wheat was enhanced by plant breeding in the first quarter of the 20th century and following a decrease during the second quarter was increased again by plant breeding.